[Im kyank’y vorpes beverrayin hetazotogh] - Amundsen, Roald; Movsisyaně, Suren (Toner, 2008)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Historical Polar bases - preservation and management - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2008)
Publication Title: Monuments and sites
Keywords: Antarktis; forskningsstasjoner; kulturminnevern; kulturvern; polarområdene

Review of Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition, by M.L. Paine - Baughman, Timothy H (Polar Research, 2008)
If the reader is looking for another rehashing of one of the adventures of the “Heroic Era” of Antarctic exploration, or another reshaping of the same old material about the three or four explorers from that period who get all the attention, M.L. Paine’s Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition is not the book for you. But if you are a serious Antarctic buff who wants to learn something new, and really get inside one of the early expeditions of the 20th century, Paine’s volume will be a compelling read.
Keywords: Antarktis; Richard Evelyn Byrd; Sydpolflyvningen; bokanmeldelser; dagbøker; ekspedisjoner; fly; luftfart; oppdagelsesreiser; polarflyving; turisme

Cenozoic Climate History from Seismic Reflection and Drilling Studies on the Antarctic Continental Margin - Cooper, Alan K; Brancolini, Giuliano; Escutia, Carlota; Kristoffersen, Yngve; Larter, Rob; Leitchenkov, German; O'Brien, Phillip; Jokat, Wilfried (Developments in Earth and Environmental Sciences, 2008)
Keywords: Antarktis; geomorfologi; innlandsis; isbreer; kontinentalmargin; paleoseanografi; stratigrafi

Ground-based measurements of spatial and temporal variability of snow accumulation in East Antarctica - Eisen, Olaf; Frezzotti, Massimo; Genthon, Christophe; Isaksson, Elisabeth; Magand, Olivier; van den Broeke, Michiel R; Dixon, Daniel A; Ekaykin, Alexey; Holmlund, Per; Kameda, Takao; Karlöf, Lars; Kaspari, Susan; et al. (Reviews of Geophysics, 2008)
The East Antarctic Ice Sheet is the largest, highest, coldest, driest, and windiest ice sheet on Earth. Understanding of the surface mass balance (SMB) of Antarctica is necessary to determine the present state of the ice sheet, to make predictions of its potential contribution to sea level rise, and to determine its past history for paleoclimatic reconstructions. However, SMB values are poorly known because of logistic constraints in extreme polar environments, and they represent one of the biggest challenges of Antarctic science. Snow accumulation is the most important parameter for the SMB of ice sheets. SMB varies on a number of scales, from small-scale features (sastrugi) to ice-sheet-scale SMB patterns determined mainly by temperature, elevation, distance from the coast, and wind-driven processes. In situ measurements of SMB are performed at single points by stakes, ultrasonic sounders, snow pits, and firn and ice cores and laterally by continuous measurements using ground-penetrating radar. SMB for large regions can only be achieved practically by using remote sensing and/or numerical climate modeling. However, these techniques rely on ground truthing to improve the resolution and accuracy. The separation of spatial and temporal variations of SMB in transient regimes is necessary for accurate interpretation of ice core records. In this review we provide an overview of the various measurement techniques, related difficulties, and limitations of data interpretation; describe spatial characteristics of East Antarctic SMB and issues related to the spatial and temporal representativity of measurements; and provide recommendations on how to perform in situ measurements.
Keywords: Antarktis; akkumulasjon; fjernmåling; glasiologi; havnivåstigning; innlandsis; paleoklimatologi; snø

Apatite single-grain (U-Th)/He data from Heimefrontfjella, East Antarctica: Indications for differential exhumation related to glacial loading? - Emmel, Benjamin; Jacobs, Joachim; Crowhurst, P; Austegard, Atle; Schwarz-Schampera, Ulrich (Tectonics, 2008)
Single-grain (U-Th)/He ages from two profiles were used to reconstruct the post-Permian tectonic-thermal history of basement rocks in Heimefrontfjella, East Antarctica. The (U-Th)/He ages from one sample collected below the late Carboniferous/Early Permian sedimentary cover rocks indicate Jurassic–Early Cretaceous basement paleotemperatures of ∼40°–60°C due to post-Permian burial. Combined apatite fission track and (U-Th)/He analyses from samples of a profile in Sivorgfjella suggest a period of flexural-related tilting after ∼87 Ma. The timing was further constrained using forward and inverse models of the (U-Th)/He data. Model results indicate a Cenozoic phase of relatively rapid cooling from ∼40°C to surface temperatures. As the driving mechanism, we propose flexural isostatic rebound due to glacial load during the development of the intracontinental ice sheet in the hinterland of the Heimefrontfjella region.
Keywords: Antarktis; geologi; tektonikk; termokronologi

Predicting the fate of ice shelves - Galton-Fenzi, Benjamin K (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

From the editor: halfway through the IPY—halfway for an Antarctic traverse - Goldman, Helle V (Polar Research, 2008)
April is here and we have just passed the midpoint of the International Polar Year (IPY), which began on 1 March 2007 and will conclude on 1 March 2009. The “year” stretches over 24 months to accommodate two summer field seasons in both polar regions. The northern summer is fast approaching, and scientists who will undertake a second IPY summer season in the Arctic are making their final preparations. At the opposite end of the planet, summer is over and scientists have wrapped up the first IPY field season. Those whose projects will carry on for a second summer season will have to wait until late this year to resume work in Antarctica.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Polar exploration - Huntford, Roland (Two planks and a passion : the dramatic history of skiing, 2008)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; skihistorie; utstyr

Antarctic ices shelves in a changing climate - Jenkins, Adrian (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

In situ measurements of snow surface roughness using a laser profiler - Lacroix, Pascal; Legrésy, B; Langley, Kirsty; Hamran, Svein Erik; Kohler, Jack; Roques, S; Rémy, F; Dechambre, M (Journal of Glaciology, 2008)
The snow surface roughness at centimetre and millimetre scales is an important parameter related to wind transport, snowdrifts, snowfall, snowmelt and snow grain size. Knowledge of the snow surface roughness is also of high interest for analyzing the signal from radar sensors such as SAR, altimeters and scatterometers. Unfortunately, this parameter has seldom been measured over snow surfaces. The techniques used to measure the roughness of other surfaces, such as agricultural or sand soils, are difficult to implement in polar regions because of the harsh climatic conditions. In this paper we develop a device based on a laser profiler coupled with a GPS receiver on board a snowmobile. This instrumentation was tested successfully in midre Lovénbreen, Svalbard, in April 2006. It allowed us to generate profiles of 3 km sections of the snow-covered glacier surface. Because of the motion of the snowmobile, the roughness signal is mixed with the snowmobile signal. We use a distance/frequency analysis (the empirical mode decomposition) to filter the signal. This method allows us to recover the snow surface structures of wavelengths between 4 and 50 cm with amplitudes of >1 mm. Finally, the roughness parameters of snow surfaces are retrieved. The snow surface roughness is found to be dependent on the scales of the observations. The retrieved RMS of the height distribution is found to vary between 0.5 and 9.2 mm, and the correlation length is found to be between 0.6 and 46 cm. This range of measurements is particularly well adapted to the analysis of GHz radar response on snow surfaces.
Keywords: Antarktis; glasiologi; teknologi

The use and abuse of dogs on Scott's and Amundsen's South Pole expeditions - Murray, Carl (Polar Record, 2008)
In the century since Roald Amundsen and Robert F. Scott led the first and second expeditions to reach the South Pole, commentators have frequently passed judgement on the different means of transport that the two explorers employed. In hindsight, and since he ‘won,’ they have consistently praised Amundsen for using dogs exclusively and criticised Scott for not doing the same. Surprisingly, however, almost no attention has been given to the experience of Amundsen's dogs, whose extreme suffering seems to have vanished into a collective blind spot. Here, with the aim of restoring balance to one part of the vexed historiography of the two explorers, that record is set straight. Amundsen's troubled and contradictory attitude towards his animals is also explored and common misconceptions about Scott's views on the use of dogs for transport are confuted.
Publisher: Cambridge University Press
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie; sledehunder

Temperature effects on biodegradation of petroleum contaminants in cold soils - Rike, Anne Gunn; Schiewer, Silke; Filler, Dennis M (Bioremediation of Petroleum Hydrocarbons in Cold Regions, 2008)
Bioremediation in cold climates is frequently regarded with skepticism. Owners of polluted sites and regulatory agencies may doubt the effectiveness of biological degradation at near freezing temperatures. While it is true that biodegradation rates decrease with decreasing temperatures, this does not mean that bioremediation is inappropriate for cold regions. Microbial degradation of hydrocarbons occurs even around 0 °C (Chapter 4). In remote alpine, Arctic, and Antarctic locations, excavation and shipping of contaminated soil may be prohibitively expensive. Bioremediation may be the most cost-effective alternative. This chapter discusses microbial adaptation to cold temperatures as well as results of laboratory and field studies of bioremediation at low temperatures.Microorganisms can grow at temperatures ranging from subzero to more than 100 °C. Microbes are divided into four groups based on the range of temperature at which they can grow. The psychrophiles grows at temperatures below 20 °C, the mesophiles between 20 °C and 44 °C, the thermophiles between 45 °C and 70 °C, and the hyperthermophiles require growth temperatures above 70 °C to over 110 °C. The term “cold-adapted microorganisms” (CAMs) is frequently used for describing bacteria growing at or close to zero degrees Celsius. Depending on the cardinal temperatures (the minimal, the optimal, and the maximum growth temperature), CAMs can be classified as psychrophiles or psychrotrophs. Morita's (1975) definition, which holds that psychrophiles have a maximum growth temperature of less than 20 °C and an optimal growth temperature of less than 15 °C, while psychrotrophs have a maximum temperature of 40 °C and an optimal growth temperature higher than 15 °C, is widely accepted.
Keywords: Antarktis; biodiversitet; forurensning; polarområdene; økologi; økosystemer

Contamination, regulation, and remediation: an introduction to bioremediation of petroleum hydrocarbons in cold regions - Snape, Ian; Acomb, Larry; Barnes, David L; Bainbridge, Steve; Eno, Robert; Filler, Dennis M; Plato, Natalie; Poland, John S; Raymond, Tania C; Rayner, John L; Riddle, Martin J; Rike, Anne G; et al. (Bioremediation of Petroleum Hydrocarbons in Cold Regions, 2008)
Oil and fuel spills are among the most extensive and environmentally damaging pollution problems in cold regions and are recognized as potential threats to human and ecosystem health. It is generally thought that spills are more damaging in cold regions, and that ecosystem recovery is slower than in warmer climates (AMAP 1998; Det Norske Veritas 2003). Slow natural attenuation rates mean that petroleum concentrations remain high for many years, and site managers are therefore often forced to select among a range of more active remediation options, each of which involves a trade-off between cost and treatment time (Figure 11). The acceptable treatment timeline is usually dictated by financial circumstance, perceived risks, regulatory pressure, or transfer of land ownership.In situations where remediation and site closure are not urgent, natural attenuation is often considered an option. However, for many cold region sites, contaminants rapidly migrate off-site (Gore et al. 1999; Snape et al. 2006a). In seasonally frozen ground, especially in wetlands, a pulse of contamination is often released with each summer thaw (AMAP 1998; Snape et al. 2002). In these circumstances natural attenuation is likely not a satisfactory option. Simply excavating contaminants and removing them for off-site treatment may not be viable either, because the costs are often prohibitive and the environmental consequences of bulk extraction can equal or exceed the damage caused by the initial spill (Filler et al. 2006; Riser-Roberts 1998).
Keywords: Antarktis; biodiversitet; forurensning; polarområdene; økologi; økosystemer

Land-fast ice variation during the past five decades: Lützow-Holm Bay, Antarctica - Ushio, Shuki (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Vår glemte polarhelt : Carsten Borchgrevink og Southern Cross-ekspedisjonen 1898-1900 - Vogt, David (Aschehoug, 2008)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Nordmenn; Ole Must; Per Savio; Southern Cross; Sydpolen; biografier; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarforskning; polarområdene; samisk

Klimagåten Antarktis - Winther, Jan-Gunnar (Gyldendal, 2008)
Keywords: Antarktis; IPY; Sydpolen; ekspedisjoner; internasjonale polarår; isbreer; klimaendringer; klimatologi; polarforskning

Norge i Antarktis : fra erobring til moderne forskning - Winther, Jan-Gunnar; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Tveraa, Torkild; Monsen, Oddbjørn (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norway in the Antarctic : from conquest to modern science - Winther, Jan-Gunnar; Tveraabak, Jacob; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Monsen, Oddbjørn; Goldman, Helle V (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene